A substrate-bound structure of cyanobacterial biliverdin reductase identifies stacked substrates as critical for activity - Haruna Takao (Nature Portfolio, 2017)
Biliverdin reductase (BVR) catalyses the last step in haem degradation. Here the authors present the crystal structure of cyanobacterial BVR bound to its substrate biliverdin and oxidised cofactor NADP+, which was used to propose the catalytic mechanism of this enzyme.